Histomorphology of Testes in Cattle Egret (Bubulcus ibis) - Nidhi Gupta (Indian Journal of Veterinary Anatomy, 2022)
The present study was conducted on male cattle egret (Bubulcus ibis). After dissection of the bird, the topography of testes was recorded and then fixed in 10% neutral buffered formalin. Sections of 4-6 µm in thickness were obtained and stained with Harris heamatoxylin and Eosin stain (H&E), Van Gieson’s and Schmorl’s method. The left testis was placed slight cranially than the right one and was larger in size. The thickness of capsule ranged between 22.80- 28.40 µm. The capsule was made up of dense connective tissue and organised into three layers of tissue, namely outer tunica serosa, the middle and thickest layer, the tunica albuginea, and the poorly differentiated inner tunica vasculosa. Convoluted seminiferous tubules were lined by a stratified epithelium of spermatogenic cells and Sertoli cells. The height of epithelium rangedbetween 14.64- 20.40 µm. Diameter of seminiferous tubules rangedbetween 46.6- 56.50 µm. There was presence of melanin in the interstitium and capsule which correlated with black color appearance of testes macroscopically.